RANCANG BANGUN SISTEM MONITORING CAIRAN INFUS OTOMATIS BERBASIS ESP32 DANAPLIKASI SPIN (SMART PANTAU INFUS) - M Arif Rahman Hakim (2024)
Monitoring the intravenous fluids of patients who are being treated in the hospital is important because if the intravenous fluids are changed too late or experience problems can be fatal to patients. Many problem factors can occur in infusion devices in medical treatment such as inappropriate drip infusions, empty infusion tubes that are late for replacement, and so on. Therefore, in the development of technological innovation in the health sector, the author made an ESP32-based automatic intravenous fluid detection device integrated with nurses' smart phones. With the aim of knowing the amount of infusion volume, drip infusion fluids, knowing the presence of blood in the infusion tube, making it easier to adjust the number of droplets automatically using a servo motor connected to a smart phone, making it easier for nurses to check infusions, increasing the efficiency of infusion monitoring, and minimizing cases of late replacement of intravenous fluids and other problems. This research uses development research methods produced on previous products by utilizing hardware and software development. The benefits of this research can help medical personnel in the treatment of infusions in patients and for researchers to be useful for broadening horizons and developing software innovations. SPIN (Smart Pantau Infus) is a development of a tool that has been designed by previous researchers by considering new shortcomings and innovations.